2007
DOI: 10.1002/jat.1192
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxic effect of cyclosporin A in the mitochondrial respiratory chain

Abstract: Long-term treatment with CyA at doses of 15 and 20 mg kg(-1) day(-1), amounting to concentrations in blood of 445 +/- 33 and 598 +/- 53 ng ml(-1), causes alterations in the mitochondria, revealed by the increase in serum GLDH and by the functional alteration of enzyme complexes I and II of the mitochondrial respiratory chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…GLDH and OCT are mitochondrial enzymes. An increased plasma activity of these enzymes reflects structural damage to the mitochondria and cell membrane, leading to the leakage of these enzymes into the plasma [111,112]. OCT is particularly expressed in the liver [111].…”
Section: The In Vitro Assaysmentioning
confidence: 99%
“…GLDH and OCT are mitochondrial enzymes. An increased plasma activity of these enzymes reflects structural damage to the mitochondria and cell membrane, leading to the leakage of these enzymes into the plasma [111,112]. OCT is particularly expressed in the liver [111].…”
Section: The In Vitro Assaysmentioning
confidence: 99%
“…CYA prevents mitochondrially mediated apoptosis by blocking the permeability transition pore, 32 but may inhibit mitochondrial respiratory chain enzymes. 33 Similarly, tacrolimus prevents apoptosis 34 but can also act as a mitochondrial toxin. 35 Despite its potentially toxic effects on mitochondria, CYA was well tolerated by 4 of 9 MNGIE patients without any obvious exacerbation of the neuropathy or the metabolic status by strict monitoring and maintenance of plasma levels of CYA or tacrolimus within the therapeutic range.…”
Section: Consensus Proposalmentioning
confidence: 99%
“…In our work, we found that GGT u is an early marker of proximal tubular cell injury in cyclosporin A-induced nephrotoxicity (De la Cruz Rodríguez et al, 1996Rodríguez et al, , 2007. That is why we considered enzymuria, GGT u and NAG u , as early and sensitive markers of nephrotoxicity.…”
Section: Discussionmentioning
confidence: 70%